As tecnologias da informação e comunicação na Rede Municipal de Ensino de Curitiba: um levantamento de políticas públicas educacionais e suas recepções sob a perspectiva dos estudos em ciência, tecnologia e sociedade - Mondini, Marta Silva Lima (2016)
This research, based on the interpretative paradigm and qualitative research (MOREIRA and CALLEFFE, 2008), conducted a survey of public educational policies to expand access to Information and Communication Technologies (ICT) deployed in the Municipal Education Network (RME) Curitiba, and an analysis of approvals of these policies in the school context, under a perspective of the studies in Science, Technology and Society (CTS). Theoretical discussions were based on the references in Education and CTS, dialoguing with contributions from Feenberg (1982), Apple (1986), Saviani (1994), Belloni (1998), Freire (1984, 1987,1991,1995,1996 and 2000), Auler and Delizoikov (2002, 2006), Almeida (2012) and Vieira Pinto (2005.2010), an understanding of the critical, problematical and disalienated education can be a confrontational element and denunciation of the oppressive reality and ad social transformation. As for the methodological issue, documentary analysis was performed (LÜDKE and ANDRÉ, 2013) for the survey of these educational policies and interviews with professionals in the municipal education, analyzed through the content analysis technique (BARDIN, 2011), observing in their testimonies, receptions of policy initiatives at school. The results, based on document analysis and analysis of statements, indicate that there was investment of Municipal Secretary of Education (SME) for the inclusion of technology in schools and proposals for the training of teachers, on the use of technology; however, there is a deterministic understanding on Technology and Education at the Municipal Network, which is reflected in verticalized political decisions and a teacher training that still little expresses the interests of the subjects of Education. In this sense, it is suggested the expansion of dialogue between decision-makers and school community in relation to political decisions, for these decisions strengthen the pedagogical teams and their projects and the continue training of teachers promotes a theoretical deepening and a critical discussion about technology, besides the importance of continuity of proposals for pedagogical work involving ICT in schools and communities of Curitiba.